Cotyledonoid Dissecting Type Leiomyoma of the Uterus: A Case Report and Review of the Literature - Özçimen, Emel Ebru; Kıyıcı, Halil; Uçkuyu, Ayla; Akyürek, Cemalettin (Gynecology Obstetrics & Reproductive Medicine, 2008)
Cotyledonoid dissecting leiomyoma (Sternberg tumour) is a rare type of smooth muscle tumor. A 38-year-old woman presented with vaginal bleeding and pelvic pain. On ultrasound multiple solid nodular lesions myomas on serosal surface and in the myometrial wall of the uterus were observed. A tumor resembling cotyledons of the placenta with a size of 15x10x5 cm was observed in the operation. Total abdominal hysterectomy and salpingectomy were performed. The frozen section and pathology results were benign with absence of atypia and mitotic activity. Intraoperative frozen section was an important and helpful procedure to avoid overtreatment of patients in these unusual cases.